Antarctic Sea Ice, view from underwater - National Geographic Vol. 189 No. 5 May 1996 pg. 45; Stenzel, Maria; LaBonte, Kristen (California State University Channel Islands Library)
The underside of ice is revealed in this rare glimpse from below, shoing yellowish clouds of algae illuminated by stabs of sunlight. To survive in this frigid environment, the minute plants inhabit a labyrinth of unfrozen brine channels. Krill nibble at the bottom of the ice all winter and in turn support a sea-ice ecosystem.